A presença do helenismo de Ricardo Reis e da visão do mundo grego clássico na poesia de Sophia de Mello Breyner Andresen - Scramim, Camila Garcia (2006)
To the long of the decade of 30 emerged in Portugal, a movement of revalorization of the Realism, which called Neo-realism. This new realism presented as main characteristic a new focus of the Portuguese reality. According to Lopes (s/d, p. 1083) the New-Realism is a trend which point out certain Marxist conceptions of years 30 to 50, but in whose waters meet, such as of them also derives, other older or recent trends to the flavor of the dominant general conditions. The alternatives that, in poetry, appeared after this movement were based, in general, in the principle of autonomy of the art. It was what it verified itself in a group of poets that evolved of the eclecticism to the idealism to follow, by means of varied approaches, removals and individual aggregation, oscillating between the trends new-realists, mixed with estimated of the surrealism. Amongst the poets who had composed this group, it is distinguished Sophia de Mello Breyner Andresen, object of study of this research. Sophia de Mello Breyner Andresen is representative of the Portuguese contemporary poetry whose literary quality of the poetical work is disclosed by the great amount of received awardings, amongst them, in 1999, the Camões Prize, one of the most important prizes of Portugal. The present research justifies itself due to scarcity of studies on her poetry, consisting, of this form, in a contribution to the inquiries on the work of an important writer in the general panorama of Portuguese Literature. The objective of the dissertation is to verify in the poetry of Sophia de Mello Breyner Andresen, specifically, in the Dual work and The name of the things, the existing contact of the poetical classicism of Ricardo Reis and the influence of the culture Greek, configuring its ideological scienter when recouping these elements in its work. The analysis of poems was carried through on the basis of the comparative method. First, a structural analysis of chosen corpus was made, verifying the elements which compose the poetic text, like: metrics, rhyme, language figures, among others subsidy. After that, one searches bibliographical on Greek mythology as subsidy to interpret the ideological intention of Sophia when recouping certain Greek myths. The reading of odes of Ricardo Kings corroborates in the verification of as Sophia recoups them and with which intention, propitiating a reflection on the influence, imitation and originality concepts.